2008
DOI: 10.1128/iai.01475-07
|View full text |Cite
|
Sign up to set email alerts
|

Common Strategies To Prevent and Modulate Experimental Cerebral Malaria in Mouse Strains with Different Susceptibilities

Abstract: Cerebral malaria (CM) is a severe complication of Plasmodium falciparum infection, predominantly experienced by children and nonimmune adults, which results in significant mortality and long-term sequelae. Previous studies have reported distinct susceptibility gene loci in CBA/CaH (CBA) and C57BL/6 (B6) mice with experimental CM (ECM) caused by infection with Plasmodium berghei ANKA. Here we present an analysis of genome-wide expression profiles in brain tissue taken from B6 and CBA mice with ECM and report si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 48 publications
5
36
0
Order By: Relevance
“…Mice were monitored twice daily after day 5 postinfection (p.i. ), and clinical ECM was evaluated (3,4,31). Clinical ECM scores were defined by the presentation of the following signs: ruffled fur, hunching, wobbly gait, limb paralysis, convulsions, and coma.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were monitored twice daily after day 5 postinfection (p.i. ), and clinical ECM was evaluated (3,4,31). Clinical ECM scores were defined by the presentation of the following signs: ruffled fur, hunching, wobbly gait, limb paralysis, convulsions, and coma.…”
Section: Methodsmentioning
confidence: 99%
“…Regulatory T cells can be beneficial or detrimental to the induction of ECM depending on the method and timing of regulatory T cell depletion and the genetic background of the host (17)(18)(19)(20)(21)(22)(23)(24). Th17 cells, which induce tissue inflammation and are capable of disrupting the blood brain barrier (25), do not appear to contribute to the pathogenesis of ECM (26).…”
Section: Erebral Malaria (Cm) Remains a Major Cause Of Death Inmentioning
confidence: 99%
“…It has been shown that parasite-specific CD8 + T cells are primed by conventional dendritic cells in the spleen and that these cells are found in the brain at the onset of neurologic disease (17)(18)(19)(20). Furthermore, depletion of these cells from clinically ill mice completely protects against disease, showing that CD8 + T cells mediate end-stage immune pathology in ECM (17,18,21), although the specific molecules produced by these cells in vivo to cause cerebral disease have not been clearly defined. In a study by Nitcheu et al (22), CD8 + T cells were harvested from infected, perforindeficient mice and transferred into rag2 2/2 mice.…”
mentioning
confidence: 99%